Adsorption of basic red 46 dye using sea mango (cerbera odollam) activated carbon - Nur Azira Iqlima Azmi (School of Bioprocess Engineering, 2016)
The present study mainly focuses on developing activated carbon from a new potential agricultural waste in terms of the process involved, optimization and isotherms as well as kinetics study for sea mango activated carbon. The sea mango activated carbon was synthesized using chemical activation by soaking it in potassium hydroxide (KOH), followed by carbonization under pure nitrogen flow at different temperatures. The powdered sea mango activated carbon produced was analyzed using Scanning Electron Microscope (SEM), Brunauer-Emmet Teller (BET), Fourier Transform Infrared Spectroscopy (FTIR) and Total Ash Content Analysis (TAS) to investigate the surface morphology, specific pore surface area, surface functional groups and ash content, respectively. The performance of sea mango activated carbon towards the adsorption of Basic Red 46 dye was conducted in a batch adsorption system. The parameters varied were initial dye concentration, initial pH solution, adsorbent dosage and adsorption temperature. Optimization was also carried out to study the optimum operating conditions for batch adsorption by varying initial dye concentration, adsorbent dosage and initial pH solution by Response Surface Morphology (RSM) using Design of Expert (DOE) software. The results of isotherms and kinetics of the adsorption process were also analyzed using Langmuir isotherm, Freundlich isotherm, pseudo-first order kinetic and pseudo-second order kinetics models.